2003
DOI: 10.1016/s0378-1097(03)00506-8
|View full text |Cite
|
Sign up to set email alerts
|

Construction and characterization of aPorphyromonas gingivalis htpGdisruption mutant

Abstract: Our previous reports implicated the Hsp90 homologue (HtpG) of Porphyromonas gingivalis (Pg) in its virulence in periodontal disease. We investigated the role of the HtpG stress protein in the virulence of Pg. This report describes the (i) expression of a recombinant Pg HtpG (rHtpG), (ii) generation and characterization of a polyclonal rabbit anti-Pg rHtpG antiserum, and (iii) construction of a Pg htpG isogenic mutant and evaluation of the growth, adherence and invasion properties compared to the wild-type pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Construction of the other mutant strains was carried out in a similar manner: the BglII, NaeI, and ApaI sites in the wecA, wbaP, and wzt regions, respectively, were utilized for insertion of the ermF-ermAM cassette. Construction of the htpG mutant as a control strain was also performed, since HtpG, which is a homolog of the human heat shock protein Hsp90, was reported to have no effect on the growth of P. gingivalis or on its adherence to other bacterial and human cells (21,36). The PmaCI site in the htpG region was utilized for insertion of the ermF-ermAM cassette.…”
Section: Methodsmentioning
confidence: 99%
“…Construction of the other mutant strains was carried out in a similar manner: the BglII, NaeI, and ApaI sites in the wecA, wbaP, and wzt regions, respectively, were utilized for insertion of the ermF-ermAM cassette. Construction of the htpG mutant as a control strain was also performed, since HtpG, which is a homolog of the human heat shock protein Hsp90, was reported to have no effect on the growth of P. gingivalis or on its adherence to other bacterial and human cells (21,36). The PmaCI site in the htpG region was utilized for insertion of the ermF-ermAM cassette.…”
Section: Methodsmentioning
confidence: 99%
“…This provided clues about the gene products that require further study. The gene encoding the P. gingivalis Hsp90 homologue, which was one of the most upregulated genes in this study, had been knocked out in a previous study and, unexpectedly, failed to show any phenotype with respect to bacterial adherence or invasion of cultured human epithelial cells (165).…”
Section: Infection Regulates Stress Protein Synthesis In Parasite Andmentioning
confidence: 64%
“…An E. tarda htpG mutant was attenuated for virulence in Japanese flounder, as demonstrated by diminished recovery of bacteria from blood and reduced fish mortality; the strain also had defects in growth at elevated temperatures (27). In contrast, analysis of a Porphyromonas gingivalis htpG mutant in cell adhesion and invasion assays found that its virulence was not impaired (38). Accordingly, we performed a number of phenotypic assays to investigate possible mechanisms responsible for the attenuation of the leptospiral htpG mutant.…”
Section: Resultsmentioning
confidence: 99%
“…The whole-cell lysates and LPS samples were analyzed by 12.5% SDS-PAGE and immunoblotting using standard methods (37). The immunoblots were blocked and were probed with a rabbit antiserum against either Loa22 (11) (dilution, 1:2,000), whole cells of serovar Manilae (dilution, 1:1,000) (9), or recombinant HtpG from Porphyromonas gingivalis (dilution, 1:1,000) (38) in Tris-buffered saline-Tween (TBS-T). The membranes were washed three times in TBS-T, probed with horseradish peroxidase-conjugated anti-rabbit IgG (diluted 1:5,000) (Millipore), developed using Amersham ECL Western blotting detection reagents (GE Healthcare), and exposed to a LAS3000 chemiluminescence imager (Fujifilm).…”
Section: Sds-page and Immunoblottingmentioning
confidence: 99%